PENGARUH MODEL THINK TALK WRITE (TTW) BERBANTUAN MEDIA SCRAPBOOK TERHADAP PEMAHAMAN KONSEP DAN RASA INGIN TAHU SISWA - Nitarima Waruwu; Kartika Yuni Purwanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by students’ low conceptual understanding and curiosity during the learning process, highlighting the need for a learning model capable of increasing student activity and engagement in knowledge construction. This study aims to determine the differences in students’ conceptual understanding and curiosity between classes using the Think Talk Write (TTW) learning model aided by a Scrapbook medium and classes using conventional learning, as well as to determine the effect of this model on students’ conceptual understanding and curiosity. This study employed a quantitative approach using a quasi-experimental design with a nonequivalent control group design. The sample consisted of 53 students, comprising 28 students in the experimental class and 25 students in the control class. Data were collected using a conceptual understanding test and a curiosity questionnaire. The data were analyzed using an independent samples t-test and simple linear regression. The results showed that the average posttest score for conceptual understanding in the experimental class was 84.93, higher than that of the control class, which scored an average of 79.16. Furthermore, the statistical analysis revealed that the Think Talk Write (TTW) learning model supported by the Scrapbook media had a positive and significant effect on students’ conceptual understanding and curiosity, with a significance level of < 0.05; thus, H₀ was rejected and H₁ was accepted. Thus, there is a difference and an effect of using the Think Talk Write (TTW) learning model supported by the Scrapbook medium on students’ conceptual understanding and curiosity in elementary school.